What types of banks profit most from fees charged? A cross-country examination of bank-specific and country-level determinants - Tennant, David; Sutherland, Richard (Journal of Banking & Finance, 2014)
The perception that banks are exploiting customers through their fee-charging practices in a bid to maximize profits, has fuelled widespread public interest in identifying the banks that profit most heavily from fees. Using hierarchical cross-country regression analyses, this paper seeks to answer the question – what types of banks profit most from fees charged? It also highlights the country level factors that influence banks’ ability to profit from fees charged. The factors at the country level distinguish between those that relate specifically to the financial services industry and broader macroeconomic indicators. The paper also identifies three channels through which national culture impacts banks’ ability to make high profits from fees. This paper uses the most comprehensive set of explanatory variables in studies of this nature. It has also extended the spatial scope of previous studies on bank fees by including data on banks from 46 developed and developing countries. In light of swelling public pressure on governments to do ‘something’ about bank fees, ill-advised measures are highlighted.